Effect Of Exercise Therapy on Lipid Profile and Oxidative Stress Indicators in Patients with Type 2 Diabetes - Madeeha Jadoon; Shazia Zeb; Sajid Razaq; Munazza Khan; Muhammad Shoaib; Sara Mariyum (Journal of Rawalpindi Medical College)
Objective: To measure change in lipid profile and levels of oxidative stress by performing exercise therapy in patients with type 2 diabetes.